1997
DOI: 10.1007/s004380050502
|View full text |Cite
|
Sign up to set email alerts
|

Homology of AFLP products in three mapping populations of barley

Abstract: Segregation of 850 polymorphic AFLP (amplified fragment length polymorphism) fragments was followed in three different doubled haploid (DH) barley populations, Dicktoo x Morex (DM), Igri x Franka (IF) and Blenheim x E224/3 (BE), which had previously been used to construct linkage maps using other molecular markers. The final maps consisted of 310, 655 and 474 markers, of which 234, 194 and 376, respectively, were AFLPs. A comparison of profiles from the parental lines identified 51 similar-sized AFLPs segregat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(58 citation statements)
references
References 21 publications
(40 reference statements)
4
54
0
Order By: Relevance
“…This occurred in cases where the AFLP marker was not linked to any of the SSR markers. Previous research has shown that homologous AFLP fragments map on the same chromosomes in different populations (Waugh et al 1997). The same conclusion was reached in our mapping of AFLP markers in different barley populations (data not shown).…”
Section: Discussionsupporting
confidence: 77%
“…This occurred in cases where the AFLP marker was not linked to any of the SSR markers. Previous research has shown that homologous AFLP fragments map on the same chromosomes in different populations (Waugh et al 1997). The same conclusion was reached in our mapping of AFLP markers in different barley populations (data not shown).…”
Section: Discussionsupporting
confidence: 77%
“…In the L94 · Vada RIL population of Qi et al (1998b), E38M54-294 was associated with RLP. In the RIL population, there is no doubt that the band on gel is from L94, but in the cultivar set the band could also originate from another part of the genome and co-migrate by identical mobility (Waugh et al 1997;Koopman and Gort 2004). However, the association between E38M54-294 and the Vada markers was just as high as the mutual correlation between the Vada markers in the Rphq2 region, indicating that no other band has been interfering.…”
Section: Rphq2mentioning
confidence: 85%
“…Owing to their transferability across species, RFLPs were essential for the early synteny studies that identified evolutionary patterns and genome similarities among cereal crop species (Moore et al, 1995;Devos, 2005). Subsequently, amplified fragment length polymorphisms (AFLPs) were widely used for higher-density map development (Waugh et al, 1997;Hori et al, 2003;Takahashi et al, 2006), but this type of marker has issues with data quality. Sequence-based PCR markers-that is, sequence-tagged sites (STSs) (Mano et al, 1999) and simple sequence repeats (SSRs) (Ramsay et al, 2000)proved to be more reliable and informative and continue to serve as useful anchor loci for maps based on expressed sequence tags (ESTs).…”
Section: Introductionmentioning
confidence: 99%